Biodeterioration of Funeral Sculptures in La Recoleta Cemetery, Buenos Aires, Argentina. Pre and post-intervention studies - Guiamet, Patricia Sandra (2013)
Stone materials exposed to weathering are subject to biological colonization and consequently to biofilm formation, causing biodeterioration. The color changes on the stone substrates caused by biogenic pigments, mechanical stress on the mineral structure due to extracellular polymeric substances (EPS) and the accumulation of atmospheric pollutants by the biofilm are some of the deteriogenic effects, which modify esthetic and functional aspects of the work. The aim of this study was to determine biodeterioration and biofilm formation on marble tombstones from La Recoleta Cemetery, Buenos Aires, Argentina. The effect of the biocide benzalkonium chloride on biofilm formation was studied, and a chart produced of the treated tombstones. Pre- and post-intervention microbiological studies, scanning electron microscopy and X-ray dispersion analysis showed a significant decrease of the biofilm flora after treatment. However, algae of the genus Trentepohlia were difficult to eradicate. These studies are a valuable contribution to determine restoration criteria against biofilm formation, to characterize chromatic variations of biological origin on the stone and to formulate conservation and restoration policies.